Motor dysfunction as an intermediate phenotype across schizophrenia and other psychotic disorders: progress and perspectives - Hirjak, Dusan; Kubera, Katharina Maria; Thomann, Philipp; Wolf, Robert Christian (Schizophrenia research, 2018)
Primary motor abnormalities (PMA), as found in patients with schizophrenia, are quantitatively and qualitatively distinct markers of motor system abnormalities. PMA have been often referred to phenomena that are present across schizophrenia-spectrum disorders. A dysfunction of frontoparietal and subcortical networks has been proposed as core pathophysiological mechanism underlying the expression of PMA. However, it is unclear at present if such mechanisms are a common within schizophrenia and other psychotic disorders. To address this question, we review recent neuroimaging studies investigating the neural substrates of PMA in schizophrenia and so-called “nonschizophrenic nonaffective psychoses” (NSNAP) such as schizophreniform, schizoaffective, brief psychotic, and other unspecified psychotic disorders. Although the extant data in patients with schizophrenia suggests that further investigation is warranted, MRI findings in NSNAP are less persuasive. It is unclear so far which PMA, if any, are characteristic features of NSNAP or, possibly even specific for these disorders. Preliminary data suggest a relationship between relapsing-remitting PMA in hyper-/hypokinetic cycloid syndromes and neurodegenerative disorders of the basal ganglia, likely reflecting the transnosological relevance of subcortical abnormalities. Despite this evidence, neural substrates and mechanisms underlying PMA that are common in schizophrenia and NSNAP cannot be clearly delineated at this stage of research. PMA and their underlying brain circuits could be promising intermediate phenotype candidates for psychotic disorders, but future multimodal neuroimaging studies in schizophrenia and NSNAP patients and their unaffected first-degree relatives are needed to answer fundamental transnosologic questions.
Available online 1 November 2017
Gesehen am 27.02.2019
Epub ahead of print